2002
DOI: 10.1016/s0014-5793(02)02324-4
|View full text |Cite
|
Sign up to set email alerts
|

The P2X7 receptor from Xenopus laevis: formation of a large pore in Xenopus oocytes

Abstract: The purinergic P2X 7 receptor is an ATP-receptor channel predominantly expressed in immune cells. P2X 7 has been cloned from human, rat and mouse. Here we report cloning of the Xenopus laevis P2X 7 receptor (xP2X 7 ). xP2X 7 is only about 50% identical to the mammalian homologues, shows a broad tissue expression pattern, and has the electrophysiological characteristics typical of a P2X 7 receptor: low agonist affinity (EC 50 about 2.6 mM) and a non-desensitizing current. Moreover, expression of xP2X 7 in Xenop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 22 publications
1
21
0
Order By: Relevance
“…Transfected cells responded with robust inward currents (membrane holding potential ϭ Ϫ60 mV) and changes in fura-2 fluorescence to applications of BzATP (100 -600 M) with one exception: we failed to record agonist-gated current or a change in fura-2 fluorescence in response to BzATP (up to and including 1 mM) and ATP (6 mM) in HEK293 cells transfected with the gene encoding the Xenopus laevis P2X7aR. This was surprising because injection of frog P2X7aR cRNA results in large ATPgated currents in a Xenopus oocyte expression system (79 (Fig. 3, A and B).…”
Section: Resultsmentioning
confidence: 83%
“…Transfected cells responded with robust inward currents (membrane holding potential ϭ Ϫ60 mV) and changes in fura-2 fluorescence to applications of BzATP (100 -600 M) with one exception: we failed to record agonist-gated current or a change in fura-2 fluorescence in response to BzATP (up to and including 1 mM) and ATP (6 mM) in HEK293 cells transfected with the gene encoding the Xenopus laevis P2X7aR. This was surprising because injection of frog P2X7aR cRNA results in large ATPgated currents in a Xenopus oocyte expression system (79 (Fig. 3, A and B).…”
Section: Resultsmentioning
confidence: 83%
“…First, P2X 7 receptor mediated NMDG ϩ permeability increases and YOPRO1 uptake have been observed in oocytes that lack native Panx-1 (2,31,32). In contrast, a recent study concluded that these properties could only be measured when Panx-1 was coexpressed (18).…”
Section: Resultsmentioning
confidence: 99%
“…Intermolecular models argue that pore formation occurs by successive acquisition of subunits to existing oligomeric structures (Cockcroft and Gomperts, 1979). While recent studies suggest that pannexin1 is required for P2X 7 R pore formation (Locovei et al, 2007), there are also reports that injection of P2X 7 R mRNA alone is sufficient to allow generation of pores in oocytes (Paukert et al, 2002). Intramolecular models propose that subtle structural changes, possibly in the selectivity filter, contribute to channel-pore transition (Lester and Karschin, 2000).…”
Section: P2x7rg345y-egfp: a Valuable Tool For Separating Ion Channel mentioning
confidence: 99%